Perancangan Sistem Informasi Geografis Kondisi Jalan pada Kabupaten Labuhan Batu Utara : Tinjauan Literatur - Muhammad Irwan Padli Nasution; Muhammad Fauzan Amri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Road infrastructure is a vital element in supporting economic, social, and transportation activities in a region. Labuhan Batu Utara Regency faces challenges in managing and maintaining road conditions, especially in hard-to-reach areas. This article presents a recent literature review from the past five years on the application of Geographic Information Systems (GIS) for mapping and managing road conditions. The discussion covers technological innovations such as drone usage, machine learning, and crowdsourcing integration within GIS. Additionally, several international and national case studies are referenced to provide insights into the challenges and opportunities of GIS implementation. This article recommends strategies such as open-source GIS implementation, integration with mobile applications, and regular data updates to support efficient road condition management in Labuhan Batu Utara Regency.